Effects of Combining Online Anodal Transcranial Direct Current Stimulation and Gait Training in Stroke Patients: A Systematic Review and Meta-Analysis - Mitsutake, Tsubasa; Imura, Takeshi; Hori, Tomonari; Sakamoto, Maiko; Tanaka, Ryo (Frontiers in Human Neuroscience, 2021)
Objective: Combining transcranial direct current stimulation (tDCS) and repetitive gait training may be effective for gait performance recovery after stroke; however, the timing of stimulation for the best outcomes is still unclear. We performed a systematic review and meta-analysis to establish evidence for changes in gait performance between online stimulation (tDCS and repetitive gait training simultaneously) and offline stimulation (gait training after tDCS). Methods: We comprehensively searched the electronic databases Medline, Cochrane Central Register of Controlled Trials, Physiotherapy Evidence Database, and Cumulative Index to Nursing and Allied Health Literature, and included studies that combined anodal tDCS with motor-related areas of the lower limbs and gait training. Nine studies fulfilled the inclusion criteria and were included in the systematic review, of which six were included in the meta-analysis. Result: The pooled effect estimate showed that anodal tDCS significantly improved the 10-m walking test (p = 0.04; I2 = 0%) and 6-min walking test (p = 0.001; I2 = 0%) in online stimulation compared to sham tDCS. Conclusion: Our findings suggest that simultaneous interventions may effectively improve walking ability. However, we cannot draw definitive conclusions because of the small sample size. More high-quality studies are needed on the effects of online stimulation, including various stimulation parameters.